International Organizations : Principles and Issues - Bennette, A. LeRoy (New Jersey Prentice - Hall International Inc., 1988)
This book focuses on the philosophy and principles of international organizations and on the broad range of issues with which these organizations try to deal.
gp. 23/01/2019
Loans
Keywords: International Organisation; United Nations; League of Nations